2020
DOI: 10.1039/d0sm01161d
|View full text |Cite
|
Sign up to set email alerts
|

On the lipid flip-flop and phase transition coupling

Abstract: We measured the lipid flip-flop of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) in solid supported lipid bilayers across their main gel to fluid (Lβ→ Lα) phase transition. By performing time and temperature resolved neutron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Upon “flip–flop”, the composition of the inner and outer leaflets is mixed, which can be followed by monitoring the amount of −CH 3 (as opposed to −CD 3 ) groups on the surface. ,, The same idea has also been used in neutron reflectometry by Gerelli and co-workers who deposited a H/D labeled bilayer on silica and studied the loss in contrast over time. However, here it was found that interbilayer exchange was rate limiting and lipid “flip–flop” was too fast within the experimental time window. , “Flip–flop” can also be detected by TR-SANS using asymmetric vesicles where one leaflet contains a deuterated lipid . Similar to the KZAC TR-SANS technique, “flip–flop” can then be monitored by the loss in the overall intensity, which in this contrast condition is not sensitive to intervesicular exchange processes.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Upon “flip–flop”, the composition of the inner and outer leaflets is mixed, which can be followed by monitoring the amount of −CH 3 (as opposed to −CD 3 ) groups on the surface. ,, The same idea has also been used in neutron reflectometry by Gerelli and co-workers who deposited a H/D labeled bilayer on silica and studied the loss in contrast over time. However, here it was found that interbilayer exchange was rate limiting and lipid “flip–flop” was too fast within the experimental time window. , “Flip–flop” can also be detected by TR-SANS using asymmetric vesicles where one leaflet contains a deuterated lipid . Similar to the KZAC TR-SANS technique, “flip–flop” can then be monitored by the loss in the overall intensity, which in this contrast condition is not sensitive to intervesicular exchange processes.…”
Section: Introductionmentioning
confidence: 76%
“…However, here it was found that interbilayer exchange was rate limiting and lipid "flip−flop" was too fast within the experimental time window. 33,34 "Flip−flop" can also be detected by TR-SANS using asymmetric vesicles where one leaflet contains a deuterated lipid. 10 Similar to the KZAC TR-SANS technique, "flip−flop" can then be monitored by the loss in the overall intensity, which in this contrast condition is not sensitive to intervesicular exchange processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In DPPC and DMPC vesicles, the values of 122 kJ/mol 8 and 64 kJ/mol 50 have been reported, whereas a lower value of 50 ± 5 kJ/mol was reported from experiments on supported lipid membranes. 51 These values highlight that not only the lipid type but also the employed experimental technique could affect the result. Still, the range of experimental values in lipid-only membranes is in the same ballpark as our value for the protein-containing membrane.…”
Section: Resultsmentioning
confidence: 99%
“…15 For phospholipids, a wide range of flip-flop rates has been reported, with the typical time scale for one flip-flop varying from minutes to days. 15,[30][31][32][33][34][35][36][37][38] Likewise, the published values for the inverse flip-flop rates of cholesterol and related sterols were observed to vary from seconds 39,40 to milliseconds. 41 One important conclusion from our simulation study is that the stress asymmetry between the two leaflet tensions of a bilayer membrane represent key parameters for the flip-flop rates.…”
Section: Introductionmentioning
confidence: 99%